706. Ceftazidime-Avibactam (CZA) and Meropenem (MER) Are Synergistic and Bactericidal Against Genetically Diverse KPC-Producing Klebsiella pneumoniae (Kp). (26th November 2018) - Jones, Chelsea; Kline, Ellen; Morder, Kristin; Clancy, Cornelius J; Nguyen, M Hong; Shields, Ryan K
Abstract: Background: We previously showed that CZA MICs are higher among KPC-3 Kp and KPC-2 Kp with porin mutations. Clinical resistance has emerged among KPC-3 Kp. Here, we tested various agents in combination with CZA for synergistic and bactericidal activity. Methods: We tested isolates for responses to CZA alone (1 and 4× MIC; avibactam fixed at 4 µg/mL), and in combination with colistin (COL; 2 µg/mL), fosfomycin (FOS; 100 µg/mL + 25 µg/mL G6P), gentamicin (GEN; 2 µg/mL), MER (8 µg/mL), and tigecycline (TGC; 2 µg/mL) by time-kill using a starting inoculum of 1 × 10 8 cFu/mL. Log-kills were calculated as log cFu/mL decrease from time 0; 24 hours was the primary endpoint. Results: Thirty KPC-Kp isolates were studied (22 KPC-2 and 8 KPC-3); all isolates were CZA-susceptible (MIC range: 0.125–4 µg/mL). Fifty-three percent harbored ompK36 mutations (eight each with IS 5 and 134–135 DG insertions). Mean log-kills by CZA at 1× and 4× MIC were 2.00 and 2.35, respectively; CZA was bactericidal (≥3-log kill) at 24 hours against 33% and 50%, respectively. CZA mean log-kills at 4× MIC were greater for KPC-3 (3.81) than KPC-2 (1.82) isolates ( P = 0.03), but did not vary by porin genotype ( P = 0.44). GEN was the most active single agent and was bactericidal against 57%; the mean log-kill was 3.06. In combination with CZA, rates of synergy (>2-log kill in combo) with COL, FOS, GEN, MER, and TGC were 83%, 60%, 40%, 87%, and 7%, respectively. The corresponding rates of bactericidal activity were 87%, 77%, 80%, 100%, and 30%, respectively. Antagonism (>1-log kill by most active single agent) was identified in 7%, 23%, 20%, 0%, and 27% with CZA + COL, FOS, GEN, MER, and TGC, respectively. Mean log-kills by CZA + MER were greater among isolates with wild-type (6.58) vs. mutant (5.48) ompK36 ( P = 0.0006), and isolates harboring KPC-3 (7.02) vs. KPC-2 (5.63; P = 0.0004). CZA + COL responses were attenuated among isolates with COL MICs ≥2 (log-kills 2.88 vs. 7.94; P = 0.0009), but not affected by ompK36 genotype ( P = 0.53). Among isolates with COL MICs <2; log-kills were greater for CZA + COL (7.94) than CZA + MER (6.44; P < 0.0001). Conclusion: A two-drug combination of CZA + MEM results in high rates of synergy and bactericidal activity against genetically diverse KPC-Kp. Mean log-kills were less among isolates with mutations in ompK36. CZA + COL was highly active against isolates ompK36 mutations, but contingent on COL susceptibility. Disclosures: M. H. Nguyen, Merck: Grant Investigator, Research grant. Astellas: Grant Investigator, Research grant. R. K. Shields, Allergan: Grant Investigator, Research grant. Pfizer: Consultant and Scientific Advisor, Speaker honorarium. Shionogi: Scientific Advisor, Consulting fee. Roche: Grant Investigator, Research grant. Venatorx: Grant Investigator, Research grant. Medicines Company: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Accelerate Diagnostics: Scientific Advisor, Consulting fee.